Glycan structures and their interactions with proteins. A NMR view. (June 2020) - Gimeno, Ana; Valverde, Pablo; Ardá, Ana; Jiménez-Barbero, Jesús
Highlights: NMR methods are of paramount importance to deduce structure, dynamics and recognition of complex glycans. The intrinsic low sensitivity of NMR for studying glycans and their interactions is overcome by using labelling strategies. Paramagnetic NMR using lanthanide-binding tags allow deducing the conformation of glycans and their recognition features. ssNMR, DNP and alternative NMR methodologies have been developed to study glycoconjugates in the cell microenvironment. Abstract : Carbohydrate molecules are essential actors in key biological events, being involved as recognition points for cell–cell and cell–matrix interactions related to health and disease. Despite outstanding advances in cryoEM, X-ray crystallography and NMR still remain the most employed techniques to unravel their conformational features and to describe the structural details of their interactions with biomolecular receptors. Given the intrinsic flexibility of saccharides, NMR methods are of paramount importance to deduce the extent of motion around their glycosidic linkages and to explore their receptor-bound conformations. We herein present our particular view on the latest advances in NMR methodologies that are permitting to magnify their applications for deducing glycan conformation and dynamics and understanding the recognition events in which there are involved.